Hubungan Kemampuan Penalaran Formal Dengan Prestasi Kimia Siswa Kelas XII Dan Kontribusinya Terhadap Tingkat Pemahamannya Di Pendidikan Tinggi - Pratiwi, Yunilia Nur; Analita, Rizky Nur; Rohmah, Rosyidah Syafa’atur; Rahayu, Widi (FKIP Universitas Palangka Raya, 2024)
This study aims to determine the level of formal reasoning ability of high school students and its relationship to their chemistry learning outcomes on the topic of colligative properties. This non-experimental survey research involved 67 12th-grade science students who plan to continue their education to higher education as respondents. The data collection instruments consisted of the Test of Logical Thinking (TOLT), which describes the students' formal reasoning abilities, and the colligative properties achievement test, which indicates the students' learning achievements. The results showed a significant positive correlation between formal reasoning skills and students' learning achievements, with a high correlation level (r = 0.544). Based on the coefficient of determination, it was found that nearly 30% of students' colligative properties achievements are influenced by their formal reasoning abilities. Further analysis revealed that proportional and probabilistic reasoning had a higher percentage (both 61.94%) compared to control variables and correlational reasoning (both 52.985%). The regression analysis results indicated that reasoning ability significantly influences students' understanding of colligative properties with the equation y = 4.386 + 0.744x. This indicates that reasoning ability positively contributes to predicting their understanding of concepts in higher education. Additionally, other cognitive factors that are presumed to influence students' preparation before entering college or university need to be understood.